Sample Preparation Strategies for Antibody-Free Quantitative Analysis of High Mobility Group Box 1 Protein - Ingeborg Kvivik; Grete Jonsson; Roald Omdal; Cato Brede (MDPI AG, 2021)
Sickness behavior and fatigue are induced by cerebral mechanisms involving inflammatory cytokines. High mobility group box 1 (HMGB1) is an alarmin, and a potential key player in this process. Reliable quantification methods for total HMGB1 and its redox variants must be established in order to clearly understand how it functions. Current methods pose significant challenges due to interference from other plasma proteins and autoantibodies. We aimed to develop an antibody-free sample preparation method followed by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) to measure HMGB1 in human plasma. Different methods were applied for the removal of interfering proteins and the enrichment of HMGB1 from spiked human plasma samples. A comparison of methods showed an overall low extraction recovery (<40%), probably due to the stickiness of HMGB1. Reversed-phase liquid chromatography separation of intact proteins in diluted plasma yielded the most promising results. The method produced an even higher degree of HMGB1 purification than that observed with immunoaffinity extraction. Detection sensitivity needs to be further improved for the measurement of HMGB1 in patient samples. Nevertheless, it has been demonstrated that a versatile and fully antibody-free sample preparation method is possible, which could be of great use in further investigations.